Unraveling the mystery of vernix caseosa - Singh Gurcharan; Archana G (Wolters Kluwer Medknow Publications, 2008)
Vernix caseosa is a white, creamy, naturally occurring biofilm covering the skin of the fetus during the last trimester of pregnancy. Vernix coating on the neonatal skin protects the newborn skin and facilitates extra-uterine adaptation of skin in the first postnatal week if not washed away after birth. It consists of water-containing corneocytes embedded in a lipid matrix. The strategic location of the vernix on the fetal skin surface suggests participation in multiple overlapping functions required at birth, such as barrier to water loss, temperature regulation, and innate immunity. Vernix seems to perform various integral roles during transition of the fetus from intra-uterine to extra-uterine life. It has also found various interesting diagnostic and prognostic implications in this arena. Thus, it continues to be an intriguing topic of interest among the medical fraternity to understand its detailed biology and function in the fetus and also to put its naturally endowed characteristics to use in the adult population.